The Portrayal of Racial Discrimination in Paul Beatty’s Tuff: A Postcolonial Study (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The present research paper entitled ‘The Portrayal of Racial Discrimination in Paul Beatty’s Tuff: ‘A Postcolonial Study’ explores the novel from the perspective of postcolonial theory. Through the protagonist, Winston Foshay Tuffy, Beatty depicts racial discrimination as characters suffer from racism, dehumanization, black identity crises, fear, violence and death. This paper shows that racism is still prevalent in American society and has not ended. There are examples of regression instead of progression. Black characters are marginalized, oppressed, victimized and demoralized in the USA. It describes how Black face misery and discrimination based on race. This paper analyses how African Americans have been gravely damaged, having confronted barbarity, violence, torture and segregation from white people. So, the paper’s objective is to portray racial discrimination and show that blacks suffer from different problems because of their skin colour. The study poignantly depicts the deplorable conditions of the African-Americans who struggle and strive for their identity and equality.